2013
DOI: 10.4103/0972-2327.120467
|View full text |Cite
|
Sign up to set email alerts
|

"Dry" and "wet" beriberi mimicking critical illness polyneuropathy

Abstract: Three cases with manifestations of right heart failure, shock, metabolic acidosis, and renal failure in varying combination were admitted with paraparesis. Nerve conduction study suggested predominantly motor and mainly axonal type of neuropathy. Rapid reversal of shock, acidosis, and multi-organ dysfunction with timely infusion of thiamine was followed by the complete neurological recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…4,5 Although dry and wet forms of beriberi can occur in the same patient at the same time, this seems to be rare. 6…”
Section: Terminologymentioning
confidence: 99%
“…4,5 Although dry and wet forms of beriberi can occur in the same patient at the same time, this seems to be rare. 6…”
Section: Terminologymentioning
confidence: 99%
“…In the current study, five patients were observed to have concomitant wet beriberi, and two exhibited co-occurring Wernicke encephalopathy and one presented with rhabdomyolysis. The presence of concomitant wet beriberi has been previously documented by Prakasha et al [25], who reported three cases with manifestations of right heart failure, shock, metabolic acidosis, and renal failure in varying combination with paraparesis, and successful recovery through prompt intervention with thiamine supplementation within a range of 24 h to several weeks. Furthermore, the co-occurrence of Wernicke encephalopathy and neuropathy has also been reported in research conducted by Söylemez et al [26], in a patient with a history of chronic daily alcohol consumption.…”
Section: Discussionmentioning
confidence: 68%
“…The presence of concomitant wet beriberi has been previously documented by Prakasha et al. [25], who reported three cases with manifestations of right heart failure, shock, metabolic acidosis, and renal failure in varying combination with paraparesis, and successful recovery through prompt intervention with thiamine supplementation within a range of 24 h to several weeks. Furthermore, the co‐occurrence of Wernicke encephalopathy and neuropathy has also been reported in research conducted by Söylemez et al.…”
Section: Discussionmentioning
confidence: 80%
“…Few studies report patients presenting with symptoms of both wet beriberi and dry beriberi. In the available reports, symptoms involved right-sided heart failure and axonal polyneuropathy [5,6]. This case was previously presented at the annual University of Pittsburgh Medical Center Hamot Research Conference on April 29, 2022.…”
Section: Introductionmentioning
confidence: 99%